2018
DOI: 10.1166/jnn.2018.14262
|View full text |Cite
|
Sign up to set email alerts
|

Delivery of Abscisic Acid to Plants Using Glutathione Responsive Mesoporous Silica Nanoparticles

Abstract: An intracellular glutathione (GSH) responsive phytochemical delivery system based on thiol gated mesoporous silica nanoparticles (MSNs) was developed and tested on the model plant Arabidopsis thaliana. In the present study, monodispersed MSNs with particle diameters of ~20 nm and pore sizes of ~2.87 nm were synthesized and modified. Abscisic acid (ABA), a key phytohormone, was entrapped in the mesopores of MSNs and then the pore entrances of MSNs were covered with decanethiol gatekeepers through GSH-cleavable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(38 citation statements)
references
References 0 publications
2
36
0
Order By: Relevance
“…Several redox-responsive systems have been developed, employing gatekeepers including organic components, inorganic crystals, polymers, and biomolecules [48]. Some examples of gatekeepers are cyclodextrins [49], curcumin [50], ZnO quantum dots [51], PEG [52], and hyaluronic acid [53].…”
Section: Types Of Stimuli-responsive Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several redox-responsive systems have been developed, employing gatekeepers including organic components, inorganic crystals, polymers, and biomolecules [48]. Some examples of gatekeepers are cyclodextrins [49], curcumin [50], ZnO quantum dots [51], PEG [52], and hyaluronic acid [53].…”
Section: Types Of Stimuli-responsive Systemsmentioning
confidence: 99%
“…Stimuli-responsive nanoparticles can be applied to soils in order to provide targeted and slow release of fertilizers, fungicides, herbicides, and plant growth regulators. Sun et al [48] developed a redox-responsive system for encapsulation of abscisic acid, a plant growth regulator responsible for regulating physiological changes in plants and increasing glutathione levels under stress conditions. Trials using Arabidopsis plants under hydric stress conditions showed that treatment with the nanoparticles induced physiological changes, with closure of the stomata in order to avoid water loss, as well as high expression of the AtGALK2 gene related to stress relief.…”
Section: Applications Of Stimuli-responsive Systems In Agriculturementioning
confidence: 99%
“…In particular, mesoporous silica NP, already used as anticancer drug delivery systems, are expected to be a promising carrier of resistance inducers. [224] To date engineered NP have been successfully used as phytohormone delivery systems [225] or like pesticide carriers in order to target their activity and reduce the indiscriminate leaking of toxic compounds, alleviating the potential adverse effects on the environment. [226] Functionalized mesoporous silica NP with a redox-responsive gatekeeper system, able to specifically release the resistance inducer and avoiding premature leakage in the delivery process, demonstrated their potential application in agriculture.…”
Section: Nanomaterials and Innate Memorymentioning
confidence: 99%
“…133,[150][151][152] Recently, an intracellular glutathione (GSH) responsive abscisic acid (ABA) delivery system has been developed based on thiol gated MSNs. 153 Monodispersed MSNs with particle diameter of $ 20 nm and pore size of $ 2:87 nm were synthesized and modi¯ed using decanthiol as gatekeepers. It was found that GSH mediated the release of entrapped ABA and hence reduced the leaf stomatal aperture and water loss.…”
Section: Application In Plant Systemmentioning
confidence: 99%